2001
DOI: 10.1074/jbc.m010360200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor 1 Interferes with Sp1 Binding through a Composite Element on the Rat Poly(ADP-ribose) Polymerase Promoter to Modulate Its Activity in Vitro

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) catalyzes the rapid and extensive poly(ADP-ribosyl)ation of nuclear proteins in response to DNA strand breaks, and its expression, although ubiquitous, is modulated from tissue to tissue and during cellular differentiation. PARP-1 gene promoters from human, rat, and mouse have been cloned, and they share a structure common to housekeeping genes, as they lack a functional TATA box and contain multiple GC boxes, which bind the transcriptional activator Sp1. We have previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 76 publications
0
23
1
Order By: Relevance
“…We assumed that NFI might function as a repressor of the IRS2 gene promoter that would interfere with the activator function of SP1 as it has been described for the poly(ADP-ribose) polymerase-1 promoter (Laniel et al 2001) or the platelet-derived growth factor A promoter (Rafty et al 2002). However, our experiments prove that SP1 or NFI binding is sufficient to activate the promoter.…”
Section: Discussioncontrasting
confidence: 48%
“…We assumed that NFI might function as a repressor of the IRS2 gene promoter that would interfere with the activator function of SP1 as it has been described for the poly(ADP-ribose) polymerase-1 promoter (Laniel et al 2001) or the platelet-derived growth factor A promoter (Rafty et al 2002). However, our experiments prove that SP1 or NFI binding is sufficient to activate the promoter.…”
Section: Discussioncontrasting
confidence: 48%
“…6A). Previously, it has been shown that the rat PARP-1 gene is activated by SP1 (17) and inactivated by NF1, which competes with SP1 on a composite element in the promoter of rat PARP-1 (18). We have also shown that FASN down-regulates NF-κB expression (4).…”
Section: Fasn Overexpression Promotes Parp-1 Expression Which Mediatmentioning
confidence: 95%
“…27,28 However, unlike Sp1 that is unquestionably recognized as a TF that positively influences gene transcription (reviewed in Ref. 29), members from the NFI family have been reported to be as efficient as repressors 30,31 than as activators 32 of gene transcription.…”
Section: Introductionmentioning
confidence: 97%